Tourist’ Behavior and Its Impacts to The Sustainability of Tours and Travel Operation: Evidence from Indonesia - Atriana Djabbar; Mukarramah Machmud; Mya Rahayu (E-Journal of Tourism, 2025)
Amid growing concerns over environmental degradation, cultural erosion, and social inequality, the behavior of tourists has undergone a notable transformation. In Indonesia, one of the world's most visited archipelagic nations, tourism businesses must adapt to shifting tourist expectations that increasingly prioritize sustainability. This study employs a qualitative-exploratory case study design across three major Indonesian destinations: Yogyakarta, Bali, and Labuan Bajo. Data were collected through semi-structured interviews, participant observation, and document analysis involving travel agents, guides, and domestic and international tourists. Findings reveal that tourists, especially younger and international travelers, are becoming more critical of the social and environmental implications of their visits. Travel agents are responding by integrating sustainability narratives, building strategic local partnerships, and redesigning tour products to reflect ethical and ecological values. Notably, tour guides serve as key mediators, educating travelers and promoting responsible behavior. However, gaps in infrastructure, uneven stakeholder understanding, and increased operational costs remain significant barriers to full implementation. This study contributes a micro-level perspective on how tourist preferences directly impact the operational strategies of travel agents. It proposes a three-pillar framework, continuous education, community-based partnerships, and value-driven innovation, as a roadmap for sustainable transformation. A key limitation lies in the qualitative scope, which may not fully capture behavioral shifts at scale